Compensatory motor neuron response to chromatolysis in the murine hSOD1G93A model of amyotrophic lateral sclerosis - Javier eRiancho; Maria eRuiz-Soto; Nuria T Villagra; Jose eBerciano; Maria T Berciano; Miguel eLafarga (Frontiers in Cellular Neuroscience, 2014)
We investigated neuronal self-defense mechanisms in a murine model of amyotrophic lateral sclerosis (ALS), the transgenic hSOD1G93A, during both the asymptomatic and symptomatic stages. This is an experimental model of endoplasmic reticulum (ER) stress with severe chromatolysis. As a compensatory response to translation inhibition, chromatolytic neurons tended to reorganize the protein synthesis machinery at the perinuclear region, preferentially at nuclear infolding domains enriched in nuclear pores. This organization could facilitate nucleo-cytoplasmic traffic of RNAs and proteins at translation sites. By electron microscopy analysis, we observed that the active euchromatin pattern and the reticulated nucleolar configuration of control motor neurons were preserved in ALS chromatolytic neurons. Moreover the 5'-fluorouridine (5'-FU) transcription assay, at the ultrastructural level, revealed high incorporation of the RNA precursor 5'-FU into nascent RNA. Immunogold particles of 5’-FU incorporation were distributed throughout the euchromatin and on the dense fibrillar component of the nucleolus in both control and ALS motor neurons. The high rate of rRNA transcription in ALS motor neurons could mantain ribosome biogenesis under conditions of severe dysfunction of proteostasis. Collectively, the perinuclear reorganization of protein synthesis machinery, the predominant euchromatin architecture and the active nucleolar transcription could represent compensatory mechanisms in ALS motor neurons in response to the disturbance of ER proteostasis. In this scenario, epigenetic activation of chromatin and nucleolar transcription could have important therapeutic implications for neuroprotection in ALS and other neurodegenerative diseases. Although histone deacetylase inhibitors are currently used as therapeutic agents, we raise the untapped potential of the nucleolar transcription of ribosomal genes as an exciting new target for the therapy of some neurodegenerative diseases.